Numerical Investigations on the Influence of Soil Structure Interaction in the Dynamic Response of SDOF System. (2016) - Kavitha, P.E.; Beena, K.S.; Narayanan, K.P.
Abstract: A single concrete pile embedded in various types of soil subjected to simple harmonic dynamic load is numerically analysed and studied. The soil type, the diameter of pile, the pile head projection above the ground level and the mass at pile head are varied and analysed. The influence of soil structure interaction on the structural behaviour of pile is investigated. The finite element software specialized in soil structure interaction analysis; PLAXIS-3D is used for the present study. Two different types of dimensionless design curves are plotted and studied, The frequency ratio Vs the stiffness ratio curves for different slenderness ratio and the frequency ratio Vs the stiffness ratio curves for different mass ratio.